Navigation of Pedicle Screws in the Thoracic Spine with a New Electromagnetic Navigation System: A Human Cadaver Study. (11th February 2015) - Hahn, Patrick; Oezdemir, Semih; Komp, Martin; Giannakopoulos, Athanasios; Kasch, Richard; Merk, Harry; Liermann, Dieter; Godolias, Georgios; Ruetten, Sebastian
Abstract : Introduction. Posterior stabilization of the spine is a standard procedure in spinal surgery. In addition to the standard techniques, several new techniques have been developed. The objective of this cadaveric study was to examine the accuracy of a new electromagnetic navigation system for instrumentation of pedicle screws in the spine. Material and Method. Forty-eight pedicle screws were inserted in the thoracic spine of human cadavers using EMF navigation and instruments developed especially for electromagnetic navigation. The screw position was assessed postoperatively by a CT scan. Results. The screws were classified into 3 groups: grade 1 = ideal position; grade 2 = cortical penetration <2 mm; grade 3 = cortical penetration ≥2 mm. The initial evaluation of the system showed satisfied positioning for the thoracic spine; 37 of 48 screws (77.1%, 95% confidence interval [62.7%, 88%]) were classified as group 1 or 2. Discussion. The screw placement was satisfactory. The initial results show that there is room for improvement with some changes needed. The ease of use and short setup times should be pointed out. Instrumentation is achieved without restricting the operator's mobility during navigation. Conclusion. The results indicate a good placement technique for pedicle screws. Big advantages are the easy handling of the system.